AKUNTABILITAS PENGELOLAAN KEUANGAN DESA DALAM PEMBERDAYAAN MASYARAKAT (STUDI TENTANG PERANAN BADAN PEMBERDAYAAN MASYARAKAT, PEMERINTAHAN DESA, PEREMPUAN DAN KELUARGA BERENCANA DI KECAMATAN SELAT NASIK KABUPATEN BELITUNG) - Azhari . (Jurnal Administrative Reform, 2017)
This study for review the role of community empowernment, village government, population and woman agency in develop the village, which is background by less development in the form of guiding or mentoring that had been on the run. Based on research result obtained condusion that is the role BPMPDPKB Belitung Regency in develop the village still not a optimum about guiding and mentoring are implemented in the period 2010-2013, BPMPDPKB Belitung Regency in develop the village tending to passive waiting for the village to consult about financial management village.